Gerakan Desa Hijau: Pemberdayaan Masyarakat dalam Pelestarian Lingkungan - Fitri Dewi Inayah Nasution; Ahmad afandi surbakti (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
This study examines the Green Village Movement as a form of community empowerment in environmental conservation at Jl. Sosro Gg. Amban, Bandar Selamat Subdistrict. The increasing environmental degradation has encouraged local community-based initiatives to sustain environmental preservation. The Green Village Movement integrates active participation of residents in activities such as greening, waste management, and natural resource conservation through a bottom-up approach. This research employs a descriptive qualitative method with data collected through interviews, participatory observation, and document studies. The results indicate that the movement effectively empowers the community to actively maintain cleanliness and environmental beauty, while enhancing social solidarity. Despite challenges such as limited funding and awareness, the Green Village Movement positively impacts environmental quality and social life. This study concludes that the community empowerment model based on the Green Village Movement can be replicated as an effective sustainable rural development strategy.